Pengaruh Financial Distress, Profitabilitas, dan Leverage terhadap Tax Avoidance - Nida Fadhila; Sari Andayani (Owner : Riset dan Jurnal Akuntansi, 2022)
Although taxes are considered important, the realization of tax revenues has not been carried out optimally. This is due to the low compliance of taxpayers in Indonesia and there are taxpayers who do tax avoidance. This study aims to prove empirically the effect of financial distress, profitability, and leverage on tax avoidance. The empirical study used is multinational companies in the manufacturing industry and producers of raw materials listed on the Indonesia Stock Exchange from 2017 to 2021. This research is included in quantitative research, using secondary data in the form of an annual report obtained from the official website of the Indonesia Stock Exchange. (IDX) as well as the company's official website. The population in this study was 129 companies, including 92 multinational manufacturing companies and 37 multinational companies producing raw materials. Sampling using purposive sampling technique, namely the method of determining the sample using certain criteria determined by the researcher. After using the purposive sampling method, the sample size was 50 companies with a research period of 5 years, in order to obtain 250 observational data. The method used is multiple linear regression method. The analysis technique is descriptive statistical analysis, classical assumption test and hypothesis testing consisting of goodness of fit (F test), statistical hypothesis test (t test), and coefficient of determination (R2). Data processing was carried out with the help of SPSS version 25 software. The results showed that financial distress and leverage had a positive effect on tax avoidance, while profitability had a negative effect on tax avoidance.